EFFECT OF INTEGRATED NUTRIENT MANAGEMENT ON SOIL PROPERTIES AND NUTRIENT CONTENT IN PEA (PISUM SATIVUM L.) - SHARMA, NISHA; SINGH THAKUR; KULDEEP (The Bioscan, 2016)
A field experiment was conducted in the year 2010-2011 to evaluate the effect of Rhizobium, PSB and inorganic nutrient sources on soil properties and nutrient content under pea (Pisum sativum L.). A total of nine treatments including a control were replicated thrice in a Randomized Complete Block Design. The treatments consisted of Rhizobium and PSB with two levels of recommended dose of fertilizers (50 and 75%) and were compared with 100% RDF only (control). Seeds were sown in lines at a spacing of 60 × 7.5cm in 3.0m × 2.5m plots. Results indicated that application of Rhizobium isolate-2 + PSB + 50% N&P+ 100% K (T9) significantly increase the available N (365.84 kg/ha), P (43.75 kg/ha) in soil and N content (4.21%) in the leaves. However, this treatment was found statistically at par with treatment T7 (Rhizobium isolate -2 + PSB + 75% N & P + 100% K), which was the next best treatment for the other characters under study. Hence, the application of biofertilizers (Rhizobium and PSB) in combination with inorganic fertilizers at reduced doses (25-50%) can maintain and sustain a higher level of soil fertility and crop productivity.